PERBEDAAN TINGKAT DEPRESI MASA MENOPAUSE ANTARA IBU BEKERJA DAN IBU TIDAK BEKERJA DI RT 13-15 DESA TAMBAK BAYAAN YOGYAKARTA - Murgi Handari, Murgi Handari (Jurnal Kesehatan, 2021)
Background: Menopause is a significant physiology change for woman who has reach age of 40 – 65. Menopause is a phase in a woman life cycle which begins when woman stops menstruating permanently. One of the symptoms is that woman experiencing menopause becomes depressed. Objective: To find out the difference of depression phase during menopause between employed and unemployed wife in RT 13 – 15 Desa Tambak Bayan Yogyakarta. Methods: This research uses comparative descriptive non experimental quantitative with cross sectional approach. Total sample is 50 people. Sampling uses purposive sampling technique. Result: The depression phase during menopause of 14 employed women (28%) belongs to minor category, while 9 unemployed women (18%) are categorized as major, with significant 0,119>0,05. Conclusion Research result shows that there is no difference of depression  level during menopause between employed and unemployed wife in RT13 – 15 Desa Tambak Bayan Yogyakarta.